Extended Spectrum Beta-Lactamase Producing Enterobacteriaceae Associated with Asymptomatic Bacteriuria among Pregnant Women Attending Antenatal Clinic at Tertiary Referral Hospital, Tanzania (Tanzania Medical Journal, 2022)
BackgroundAsymptomatic bacteriuria occurs in 2-15% of pregnancies resulting in acute pyelonephritis, preterm labor, pre-eclampsia, anemia, amnionitis, low birth weight, stillbirths, bacteremia and toxic septicemia. Asymptomatic bacteriuria in pregnancy (ASBP) caused by extended-spectrum beta-lactamases producing Enterobacteriaceae (ESBL-PE) further complicates the health of a pregnant woman, affecting treatment and spread of resistant bacteria strains to newborns and the community. However, in Tanzania, screening for resistant bacteria such as ESBL-PE in ASBP is not routinely done.Broad objectiveTo determine the prevalence of ASBP associated with ESBL-PE and the antimicrobial susceptibility pattern of ESBL-PE isolated from pregnant women at Muhimbili National Hospital (MNH) in Dar es salaam, Tanzania.MethodologyA hospital-based cross-sectional study was conducted at MNH. A total of 182 pregnant women with the gestational age of 37 weeks and above were enrolled. A semi-structured questionnaire and antenatal cards were used to collect socio-demographic and pregnancy information. Clean catch mid-stream urine was collected for screening of asymptomatic bacteriuria. Bacteria were identified using conventional biochemical methods and antimicrobial susceptibility testing (AST) was performed by Kirby-Bauer method following Clinical Laboratory Standard Institute (CLSI) guidelines. The isolates resistant to ceftazidime and cefotaxime were confirmed for ESBL production using a double-disc synergy test (DDST).ResultsAsymptomatic bacteriuria was observed in 13% (24/182) of the pregnant women attending antenatal clinic at MNH. We report that, 61.9% (13/21) of women with asymptomatic bacteriuria associated with gram negative bacteria were infected with ESBL-PE. Among the ESBL-PE species mostly isolated include E. coli (69.2%), followed by K. pneumoniae (23.1%), and K. oxytoca (7.7%); and non ESBL-PE species isolated were E. coli (87.5.6%), and K. pneumoniae (12.5%). In addition, three S. aureus isolates were detected in women with ASBP. ESBL-PE isolates showed high resistance to aztreonam, sulphamethoxazole-trimethoprim, amikacin and nalidixic acid; while for the few detected non ESBL-PE high resistance was seen to sulphamethoxazole-trimethoprim, aztreonam, meropenem and nalidixic acid. Conclusion and recommendationThe present study revealed that a high proportion of bacteriuria in pregnancy is associated with ESBL-PE. These findings suggest a need for screening of resistant bacteria such as ESBL in cases of ASBP.